2004
DOI: 10.2486/indhealth.42.149
|View full text |Cite
|
Sign up to set email alerts
|

Drudgery, Accidents and Injuries in Indian Agriculture.

Abstract: The Indian farming employs 225 million workforce to cover 140 million hectares of total cultivated land. In spite of rapid farm mechanization (e.g., 149 million farm machinery), the vast resource-poor family farming has primary dependence on traditional methods (e.g., 520 million hand tools and 37 million animal-drawn implements are in operation). The work drudgery, the traumatic accidents and injuries are the major concerns to examine options for ergonomics intervention and betterment of work in crop producti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

5
42
1
2

Year Published

2009
2009
2023
2023

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 110 publications
(50 citation statements)
references
References 24 publications
(28 reference statements)
5
42
1
2
Order By: Relevance
“…Mehta et al 15) observed that the actuating force limits as given in IS 10703 8) /ISO TR 3778 9) were very high as compared to leg strength of Indian operators. Similar results were reported by other investigators 4,10,16) . However, the Bureau of Indian Standards at present has adopted recommendations of ISO/ASABE standards due to non-availability of strength data of Indian male agricultural workers.…”
Section: Introductionsupporting
confidence: 82%
See 1 more Smart Citation
“…Mehta et al 15) observed that the actuating force limits as given in IS 10703 8) /ISO TR 3778 9) were very high as compared to leg strength of Indian operators. Similar results were reported by other investigators 4,10,16) . However, the Bureau of Indian Standards at present has adopted recommendations of ISO/ASABE standards due to non-availability of strength data of Indian male agricultural workers.…”
Section: Introductionsupporting
confidence: 82%
“…It was 746 N, which was above the recommended limits as per IS 10703 8) /ISO TR 3778 9) . Nag and Nag 10) reported that tractor operation often required a large braking force (600 N or more) to be exerted by an average Indian operator weighting 50 to 60 kg. Febo and Pessina 11) also observed that actuating forces for tractor controls were higher than 600 N for pedals and 300 N for levers on 20% of the surveyed 90 tractors in use in Nothern Italy.…”
Section: Introductionmentioning
confidence: 99%
“…Further, the lack qualified workers is a concern with respect to crop mechanisation, as this could provoke more serious accidents (Nag and Nag, 2004). García and Padilla (2005), in a study on preventing work risks in Almerian greenhouses, concluded that variable environmental conditions can be extreme, and could have a negative effect on worker health and increase the risk of accidents.…”
Section: Introductionmentioning
confidence: 99%
“…Accident occurred while using any hand tool, implement or powered machinery was considered as farm implement-related agricultural accident whereas accident without use of any hand tool, farm implement and machinery was considered as other agricultural (non-farm implement-related) accident. Other agricultural accident may occur due to various reasons like snake bite, noise, vibration, and magnitude of load carrying, falling from height, falling objects and electricity (Nag and Nag, 2004). Furthermore, injury severity descriptions differ widely.…”
Section: Definition Of Termsmentioning
confidence: 99%
“…In this scale, injuries are ranked on a scale of 1-6 (1 minor, 2 moderate, 3 serious, 4 severe, 5 critical and 6 unsurvivable injuries). Mohan and Patel (1992), Varghese and Mohan (1991) and Jansson and Jacobsson (1988) have also used AIS.…”
Section: Definition Of Termsmentioning
confidence: 99%